The Use of Reproductive Health Information Material in the Rural Clinics of Umtata District - ND Mbananga (AOSIS, 1999)
Though it appears that there has been a long history of development .distribution and dissemination of reproductive health information materials, impediments still exist in the health information .communication and education systems in South Africa. The aim of the study was to contribute towards improvement of the development, distribution and utility of reproductive health information material both in the Eastern Cape province and nationally. In-depth understanding of complexities surrounding development, distribution and utility of educational material is key to the provision of information to communities.